ESB SOAS Business Based Design Platform in Management Software - et. al., Shashank Srivastava, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An infrastructure that is capable of linking any IT resource is required to merge the old and the new Service-oriented Architecture (SOA). An infrastructure that can rapidly merge and replace facilities to fulfill advanced specifications is essential for being scalable. To be confident, a reliable and secure network is required. The ESB is a network access bus. An ESB is a software interface that enables business components to be combined more efficiently and flexible in a service-based architecture. An ESB enables the complex link, mediation, control and communication of resources.